FAP homework and contingency analysis interventions (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Functional interpretation and homework’s therapeutic effects, summarized in Functional Analytic Psychotherapy’s rule 5 are little known. The objective was to investigate relations between rule 5 and clienttherapist interactions. The method consisted on recording and coding client-therapist interactions. Participants were two client-therapist dyads. An A/A+B/A/A+B design was conducted for one of the dyads, while for the other a regular FAP therapeutic process was recorded and coded. Data was analyzed by means of visual inspection of graphs, of Spearman’s correlation and of transitional probabilities analysis. Clients from both dyads emitted analysis of contingencies when evoking procedures were presented. They identified importante homework when their therapists evoked and provided consequences to self-orientation. Rule 5 did not influence analysis of contingencies, self-orientation and reports concerning improvements in daily life for dyad 1. The influence of contingency shaping analysis and self-orientation in clinical improvement is discussed.
Keywords: analysis of contingence; homework; functional analytic psychotherapy